Unraveling the characteristics of dissolved organic matter removed by aluminum species based on FT-ICR MS analysis - He, Yitian; Jarvis, Peter; Huang, Xin; Shi, Baoyou (Elsevier, 2024)
Given the complexity of dissolved organic matter (DOM) and its interactions with coagulant chemicals, the mechanisms of DOM removal by aluminum (Al) coagulants remains a significant unknown. In this study, six test waters containing DOM with molecular weight (MW, <1 kDa, 1–10 kDa and >10 kDa) and hydrophobicity (hydrophilic, transphilic and hydrophobic) were prepared and coagulated with Al0, Al13 and Al30. The molecular-level characteristics of DOM molecules that were removed or resistant to removal by Al species were analyzed using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The results showed that at the molecular level, saturated and reduced tannins and lignin-like compounds containing abundant carboxyl groups exhibited higher coagulation efficiency. Unsaturated and oxidized lipids, protein-like, and carbohydrates compounds were relatively resistant to Al coagulation due to their higher polarity and lower content of carboxyl groups. Al13 removed molecules across a wider range of molecular weights than Al0 and Al30, thus the DOC removal efficiency of Al13 was the highest. This study furthers the understanding of interactions between Al species and DOM, and provides scientific insights on the operation of water treatment plants to improve control of DOM.
Keywords: dissolved organic matter; Al species; coagulation; FT-ICR MS; PARAFAC analysis